A new name for Peperomia parvicaulis Callejas (Piperaceae) - Deshmukh, Umakant Bhoopati (Phytotaxa, 2021)
The genus Peperomia Ruiz and Pavón (1794: 8) (Piperaceae) has a pantropical distribution, with the highest diversity in the Neotropics (Wanke et al. 2006, Mathieu et al. 2015). It consists of epiphytic, epipetric or herbaceous plants with 1628 currently accepted taxa, with 1453 species plus 175 forms and varieties (Mathieu 2001-2021). Recently, Callejas (2020) described a new species from Panama, Peperomia parvicaulis Callejas (2020: 466), which is illegitimate, as it is a later homonym of the Sumatran species Peperomia parvicaulis C. de Candolle (1920: 294). Therefore, the replacement name Peperomia callejasii U.B. Deshmukh is proposed here in accordance with the article 53.1 of the Shenzhen Code (Turland et al. 2018).